2022
DOI: 10.3389/fmicb.2022.887950
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella typhimurium SL1344 by Chlorogenic Acid and the Impairment of Cellular Integrity

Abstract: Chlorogenic acid (CGA) is an antibacterial agent that can be isolated from Eucommia ulmoides Oliver, a Chinese medicinal and edible plant food. The inhibitory effect of CGA on bacterial growth and stiffness of the outer membrane (OM) had been reported, while more evidence were required to elucidate its impairment of cell wall. In this study, the morphological and physiochemical changes of Salmonella cells under CGA treatment were investigated. Firstly, the minimum inhibitory concentration (MIC) of CGA against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, the cell membrane permeability of S. cerevisiae could also interfere with pressurized CO 2 [ 25 ]. Membrane permeability ensures that substances can selectively pass through the membrane, which is very crucial for the normal physiochemical functions of cells [ 28 ]. In this work, the antifungal action of CIN + p -HPCO 2 was probably related to its capability to enhance the membrane permeability of S. cerevisiae , thereby resulting in the leakage of intracellular contents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the cell membrane permeability of S. cerevisiae could also interfere with pressurized CO 2 [ 25 ]. Membrane permeability ensures that substances can selectively pass through the membrane, which is very crucial for the normal physiochemical functions of cells [ 28 ]. In this work, the antifungal action of CIN + p -HPCO 2 was probably related to its capability to enhance the membrane permeability of S. cerevisiae , thereby resulting in the leakage of intracellular contents.…”
Section: Resultsmentioning
confidence: 99%
“…The cell plasma membrane is a crucial barrier of protection from environmental stresses [ 28 ]. Our findings suggested that the cell membrane was a primary target of CIN + p -HPCO 2 action on S. cerevisiae , which might be related to the lipophilicity of CIN or its components and CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…20,21 A large number of researchers have reported that chlorogenic acid can exhibit excellent bioactive properties in antiinflammatory, 22,23 anti-coagulant, 24,25 anti-oxidant, 26,27 antibacterial and anti-viral drugs. [28][29][30] In addition, chlorogenic acid also shows great effects in promoting endothelial cell proliferation by regulating Rap1 and PI3K/AKT signaling pathways and inducing angiopoietin-2 secretion. 31 The excellent bioactive properties of chlorogenic acid perfectly fit with the demands of BHVs.…”
Section: Introductionmentioning
confidence: 99%